2014
DOI: 10.1111/sltb.12122
|View full text |Cite
|
Sign up to set email alerts
|

Changing Rates of Suicide Ideation and Attempts Among Inuit Youth: A Gender‐Based Analysis of Risk and Protective Factors

Abstract: Inuit in Canada currently suffer from one of the highest rates of suicide in the world. The objective of this study was to explore the prevalence of suicide ideations and attempts among 15-24 year olds living in Nunavik, Québec, and to explore risk and protective factors of suicide attempts as a function of gender. A cross-sectional survey was conducted in 2004 across Nunavik. Univariate and multivariate logistic regressions were conducted. A total of 22% of young males and 39% of females adults reported past … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 57 publications
4
71
0
Order By: Relevance
“…However, some other factors are more prevalent for Inuit children and adolescents because of the culture and the historical context unique to Nunavik. For example, barriers to participation in culturally meaningful activities, acculturation and rapid social changes [1,52,53], high rates of violence in the communities [37], food insecurity [38], alcohol and substance abuse as well as sexual violence [54] could be causal factors of psychological distress of primary importance for Inuit children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…However, some other factors are more prevalent for Inuit children and adolescents because of the culture and the historical context unique to Nunavik. For example, barriers to participation in culturally meaningful activities, acculturation and rapid social changes [1,52,53], high rates of violence in the communities [37], food insecurity [38], alcohol and substance abuse as well as sexual violence [54] could be causal factors of psychological distress of primary importance for Inuit children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The use of marijuana and high levels of psychological stress were the strongest risk factors for females between 15 and 24 years of age (Fraser et al, 2015). Among males and females, physical violence and sexual abuse were significantly associated with suicide attempts.…”
Section: Mixed Methodsmentioning
confidence: 96%
“…Furthermore, Greenlandic girls were identified to be particularly vulnerable towards experiencing PTEs (S. H. Karsberg et al, 2012 (Bals, Turi, Vitterso, et al, 2011). Traditionally, Sami culture divided labour between the genders (Bals, Turi, Vitterso, et al, 2011), where hunting, for example, was a male activity, but the ongoing social changes in Inuit and Sami communities have led to changes in male and female roles (Fraser et al, 2015). Lehti et al's (2009) review revealed that substance use is common throughout the entire Arctic, where the rates in Alaska and Greenland were highest; the ethnic differences in substance use varied more locally.…”
Section: Mixed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They once prepared us to fight or flee: the heart rate and breathing accelerate, the blood pressure increases and the muscles tense [1-3,6,12,13,15-17]. Today, it is unusual to encounter a survival situation at the corner of a university corridor [18,19]. This is why symptoms such as heavy sweating, headaches (caused by blood pressure), urge to urinate, and stomach upset (caused by muscle contraction) are often more disturbing than necessary.…”
Section: Negative and Positive Side Of Stressmentioning
confidence: 99%